Methicillin-Resistant Staphylococcus aureus (MRSA) Patterns and Antibiotic Susceptibility in Surgical and Non-Surgical Patients in a Tertiary Hospital in Indonesia - Turbawaty, Dewi Kartika; Logito, Verina; Tjandrawati, Anna (Majalah Kedokteran Bandung, 2021)
Methicillin-Resistant Staphylococcus aureus (MRSA) in the hospital is found mainly in surgical patients, which increases morbidity and mortality. Currently, vancomycin is the drug of choice for the treatment of MRSA infections. The increasing use of vancomycin and its inappropriate administration may increase the resistance of S. aureus to vancomycin. This study aimed to describe the distribution of MRSA and types of antibiotics that are still sensitive to MRSA in surgical and non-surgical patients. This cross-sectional, observational, retrospective descriptive study was conducted at the Microbiology Laboratory, Dr. Hasan Sadikin General Hospital, in 2019 using secondary data on the results of culture examination and antibiotic susceptibility of positive S. aureus culture isolates from all types of isolates from surgical and non-surgical patients. All specimens were cultured in appropriate media. Identification of S. aureus was performed by Gram staining to identify bacterial morphology, and automatic tools. Antibiotic susceptibility test was performed using an automatic machine. Seventy-five isolates (17%) were identified to be MRSA with 46 (53%) of them retrieved from surgical patients. Most of the MRSA isolates came from pus and were mostly due to skin infections. Antibiotic susceptibility results showed two Vancomycin-Resistant Staphylococcus aureus (VRSA) isolates from surgical patients. The positive culture of the MRSA and VRSA was dominated by surgical patients with pus coming from surgical wound infection, burn, and other skin infection as the most common sources. Thus, the proportion of MRSA isolates in the hospital in 2019 is 17% and two VRSA isolates are identified in the same year. The surgical ward was the primary origin of most MRSA isolates. Further studies are necessary to identify the MRSA incidence rate, evaluation and periodic monitoring of antibiotic use, and active surveillance in the surgical patient rooms.